Deciphering multifarious properties of Pseudomonads suppressing tomato (Solanum lycopersicum) wilt - GUPTA, SACHIN; GUPTA, MONI; SHARMA, DEEPIKA; BHAT, NEHA (The Indian Journal of Agricultural Sciences, 2019)
Wilt is the most common disease encountered in tomato crop. To devise an eco-friendly management module against F. oxysporum f. spp. solani, the causal organism, native isolates of Pseudomonas spp. were isolated from agricultural fields. The present experiment was conducted at SKUAST-Jammu between 2014-15. Biochemical screening of isolates revealed that antimicrobial compounds, viz. 2,4-DAPG and siderophore production were maximum in isolate PS 1 (217. 70 Î¼g/ml and 32. 25 Î¼g/ml) and HCN production was highest in isolate PS 6 (0. 11 Î¼g/ml). Isolates PS 1 to PS 20 produced ferrate hydroxamate type siderophores whereas PS 21 to PS 30 produced catecholate type siderophores. Growth promoting substances, viz. IAA, GA and phosphorus solubilization were maximum in PS 7 (583. 63 Î¼g/ml), PS 15 (652. 07 Î¼g/ml) and PS 30 (358. 25 Î¼g/ml) respectively. TLC of 2,4-DAPG extracted from various isolates showed Rf values in the range of 0. 7 to 0. 89, close to the relative mobilty (Rf) of phloroglucinol (0. 89). PS 1 reported highest seed germination (75%) with vigour index of 1275. Pot experiment revealed that isolate PS 4 increased plant height, plant growth parameters and further reduced wilt incidence (34. 25%) as compared to the seedling treated with Fusarium oxysporum (60%).